IMPLEMENTASI PROGRAM TATANEN DI BALÉ ATIKAN (TDBA) MELALUI AKSI “MENANAM 1 POHON 1000 HARAPAN” DALAM MENDUKUNG PENCAPAIAN SDGS DI SDN 2 NAGRIKALER - Abdah Birrul Walidain; Azhar Syifa Fauzia; Desti Noer Ambarwati; Devianty Yusuf; Diva Aulia Aktivana; Ela Hayati; Herlina Herlina; Primanita Sholihah Rosmana (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2026)
This study aims to describe the implementation of the Tatanen di Balé Atikan (TdBA) program through the action “Planting One Tree, One Thousand Hopes” carried out by students of the Teacher Professional Program (P3K) at Universitas Pendidikan Indonesia, Purwakarta Campus, at SDN 2 Nagrikaler as an effort to support the achievement of the Sustainable Development Goals (SDGs). The activity focuses on fostering ecological awareness and developing students’ environmental care character through tree-planting activities within the school environment. This study employed a descriptive qualitative approach with data collected through interviews and documentation. The results show that the implementation of the TdBA program through the “Planting One Tree, One Thousand Hopes” action contributes to the achievement of SDGs, particularly in supporting the preservation of terrestrial ecosystems. In addition, the activity successfully increased environmental awareness among students and school communities and encouraged the use of the school environment as a learning resource. This program also highlights the important role of university students as agents of change in promoting environmental awareness within educational settings.